All about public relations : how to build business success on good communications. - Haywood, Roger, ....- (London : McGraw-Hill, 1991)
Contents: --------- 1. Public relations, a business way of life 2. The corporate personality 3. Objectives 4. Audiences 5. Managing the reputation 6. Planned action 7. Budget allocation 8. The programme 9. Employees 10. Local communities 11. Politicians, legislators and opinion leaders 12.The financial community 13. Marketing, advertising and PR 14. PR in sales support 15. Non-commercial organisations 16. Deciding with technique 17. Media relations 18. Media conferences 19. Photography 20. Radio and tv 21. Design and identity 22. Publications 23. Sponsorship 24.Special events 25. Exhibitions and presentations 26. Advertising 27. Audio-visual 28. Research 29. Professional trade groups 30. Speaker's panels 31. Issues planning 32. Measuring results 33. Summary
Keywords: Public relations